Study of Soil Acidity, Organic Carbon and Texture of Ultisol in Several Vegetation at Durian Baggal, District of Raya Kahean (Case Study: Semi Critical Land in Region Of Sibarau Water-Shed) - Rio Andreas Tambunan; Kemala Sari Lubis; Ir Razali (Universitas Sumatera Utara, 2019)
Sibarau Sub-Watershed is one of the Sub-Watershed of Padang Watershed. Land area with semi critical criteria in the Sibarau Watershed is 1471.83 hectares or 20% of the total entire Sibarau Watershed critical land area.This research was conducted to analyze and determinecharacteristic of soil physical and soil chemical in semi critical land area at sub-watershed Sibarau Durian Baggal village, Raya Kahean. research area are palm, rubber, mix plant, duku and forestry.The research was conducted at Soil Chemistry and Biology Laboratory and Research and Technology Laboratory of Faculty of Agriculture, University of North Sumatera. The Research Held in July until September 2017.The research was conducted by using survey method of sampling surveys with. Analyzed of soil pH with methods electrometry, soil organic matter with Walkley and Black method, and soil texture with Hydrometer Bouyoucos method. The results showed that on palm land soil acidity was acidic, C-organics very low and texture wasis sandy loam.On rubber land soil acidity was acidic, C-organics low and very low, texture is sandy loam. On mix plant land soail acidty is acidic, C-organics was low til very low and soil texture was sandy loam. On duku land soil acidity was acidic , C-Organics was low and soil texture was sandy loam. On forestry lan soil aciity was medium acidic, C-organics was medium and soil textutre was loamy sandKeywords: soil acidity, organic carbon, texture,semi critical land, sibarau sub-watershed